2022
DOI: 10.1002/ehf2.14003
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the genetic links of SARS‐CoV‐2 infections on heart failure co‐morbidity by a systems biology approach

Abstract: Aims The co‐morbidities contribute to the inferior prognosis of COVID‐19 patients. Recent reports suggested that the higher co‐morbidity rate between COVID‐19 and heart failure (HF) leads to increased mortality. However, the common pathogenic mechanism between them remained elusive. Here, we aimed to reveal underlying molecule mechanisms and genetic correlation between COVID‐19 and HF, providing a new perspective on current clinical management for patients with co‐morbidity. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…The TFs associated with all hub genes were FOXC1, FOS, YY1, GATA2, HNF4A, STAT3, RELA, USF2, JUN, PRDM1, and RUNX2. Based on previous studies, most of these 11 TF, especially FOXC1 and STAT3 are involved in the progression of COVID-19 and heart-related diseases ( 100 ). Eleven miRNAs were associated with all hub genes, some of which have been associated with liver cancer ( 101 103 ) (e.g., hsa-mir-27a-3p, hsa-mir-26a-5p, hsa-mir-182-5p, and hsa-mir-212-3p) and some have been closely related to lung cancer ( 104 107 ) (e.g., hsa-mir-335-5p, hsa mir-182-5p, hsa-mir-212-3p, and hsa-mir-29c-3p).…”
Section: Discussionmentioning
confidence: 99%
“…The TFs associated with all hub genes were FOXC1, FOS, YY1, GATA2, HNF4A, STAT3, RELA, USF2, JUN, PRDM1, and RUNX2. Based on previous studies, most of these 11 TF, especially FOXC1 and STAT3 are involved in the progression of COVID-19 and heart-related diseases ( 100 ). Eleven miRNAs were associated with all hub genes, some of which have been associated with liver cancer ( 101 103 ) (e.g., hsa-mir-27a-3p, hsa-mir-26a-5p, hsa-mir-182-5p, and hsa-mir-212-3p) and some have been closely related to lung cancer ( 104 107 ) (e.g., hsa-mir-335-5p, hsa mir-182-5p, hsa-mir-212-3p, and hsa-mir-29c-3p).…”
Section: Discussionmentioning
confidence: 99%
“…Based on miRBase 22.0 (http://www.mirbase.org/)), the unique sequences with the length of 18 ~ 26 nt were mapped to miRNA sequences, to recognize confirmed miRNAs and pre‐miRNAs (including novel 3p‐ and 5p‐derived miRNAs). Also, after the procedure, data normalization was applied based on the method described previously 22–24 . The remaining unmapped sequences were further screened against Homo sapiens genomic sequences to identify potential novel miRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Authors identified 10–12 genes from a protein–protein interaction study and as a shared transcriptional signature. Interestingly, the importance of the unhealthy microbiota status and a gut–heart axis were emphasized as bridging pathogenic mechanisms between HF and COVID‐19 57 …”
Section: Preclinical and Translational Investigationsmentioning
confidence: 99%
“…Interestingly, the importance of the unhealthy microbiota status and a gutheart axis were emphasized as bridging pathogenic mechanisms between HF and COVID-19. 57 Dubé et al conducted a pharmacogenomic study of HF and the angiotensin-II receptor blocker, candesartan response from the CHARM programme where their objective was to identify genetic predictors of HF progression and of the efficacy and safety of treatment with candesartan. In short, in their genome-wide association studies, including 2727 patients, they have identified a candidate genetic variant potentially predictive of the progression of HF in patients with preserved ejection fraction.…”
Section: Preclinical and Translational Investigationsmentioning
confidence: 99%